2020
DOI: 10.1161/jaha.120.016670
|View full text |Cite
|
Sign up to set email alerts
|

Prospective Screening of Extracranial Systemic Arteriopathy in Young Adults with Moyamoya Disease

Abstract: Background RNF213 is a major susceptibility gene for moyamoya disease (MMD), characterized by chronic progressive steno‐occlusion of the intracranial arteries. However, coincidental extracranial arteriopathy is sporadically described in a few cases and in children with MMD. Methods and Results This study prospectively enrolled 63 young adults (aged 20–49 years) without a known history of systemic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 32 publications
1
17
0
Order By: Relevance
“…Stenosis of extracranial vessels in association with intracranial moyamoya is uncommon, but several studies have demonstrated associated stenosis of the renal artery in a minority of patients (39,40). In addition, a few studies have demonstrated associated stenosis of external carotid artery branches, coronary arteries, and abdominal arteries (41,42). However, other studies have specifically looked for involvement of branches of the external carotid artery or intraabdominal arteries and have failed to demonstrate stenosis in these segments (40,43).…”
Section: Pathologic Characteristics Of Arterial Stenosis In Moyamoyamentioning
confidence: 99%
“…Stenosis of extracranial vessels in association with intracranial moyamoya is uncommon, but several studies have demonstrated associated stenosis of the renal artery in a minority of patients (39,40). In addition, a few studies have demonstrated associated stenosis of external carotid artery branches, coronary arteries, and abdominal arteries (41,42). However, other studies have specifically looked for involvement of branches of the external carotid artery or intraabdominal arteries and have failed to demonstrate stenosis in these segments (40,43).…”
Section: Pathologic Characteristics Of Arterial Stenosis In Moyamoyamentioning
confidence: 99%
“…In another large study in Asia, 40 of 706 pediatric patients with MMD (5.7%) had hypertension (HTN) and 22 of these 40 patients had renal artery stenosis (6). In a Korean study of adults, only 1 of 63 patients (2%) with MMD was diagnosed with renal artery stenosis (11). The large difference may be due to the difference in age stratification among study samples or it may be related to the late onset moyamoya disease in adults.…”
Section: Epidemiologymentioning
confidence: 99%
“…Bleeding is the leading cause of death in patients with moyamoya disease, and hypertension is associated with increased mortality (7). In recent years, many reports have pointed out that the changes of vascular stenosis in patients with moyamoya disease occurred not only in intracranial vessels, but also in extra cranial vessels, especially the changes of renal artery (8)(9)(10)(11). Renovascular hypertension is considered to be one of the important causes of hypertension in patients with moyamoya disease (6).…”
Section: Introductionmentioning
confidence: 99%
“…It was also recently reported that RNF213 p.(R4810K) is associated with pulmonary arterial hypertension (PAH) and peripheral pulmonary artery stenosis regardless of the presence of MMD [25], and carriers of the variant appear to have a higher risk for poor clinical outcome [26]. Moreover, other systemic arteriopathies like coronary, renal, celiac, mesenteric, and iliac artery stenosis have been reported in RNF213 p.(R4810K) homozygous and heterozygous carriers, and systematic screening for extracranial vasculopathy has been recommended in adult and pediatric MMD [27,28]. Thus, there is increasing evidence for RNF213 p.(R4810K) being related to vasculopathy with a spectrum of clinical presentations that include MDD but also other intracranial and systemic vasculopathies [29].…”
Section: Through Clinical Features and Geneticsmentioning
confidence: 99%